Research Progress of Multifunctional Hydrogels in Promoting Wound Healing of Diabetes - He J; Chen J; Liu T; Qin F; Wei W (International Journal of Nanomedicine)
Jiansong He, Jiemei Chen, Taotao Liu, Fuli Qin, Weipeng Wei Department of Pharmacy, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of ChinaCorrespondence: Weipeng Wei, Department of Pharmacy, The First Affiliated Hospital of Guangxi Medical University, No. 6 Shuangyong Road, Nanning, Guangxi, 530021, People’s Republic of China, Email wpwei625@163.comAbstract: Diabetic wound healing represents a crucial and complex subject in clinical medicine, because of its physiological mechanism and pathological state, the conventional treatment methods are often limited. In recent years, multifunctional hydrogels have emerged as a focal point in the research field regarding the healing of diabetic wounds. This is attributed to their outstanding biocompatibility, the capacity for controlling drug release, and the traits of facilitating cell migration and proliferation. This paper reviews the fundamental materials, modification strategies for functionality, the principles underlying drug release, and the latest application advancements of multifunctional hydrogels in the context of facilitating the healing process of diabetic wounds. By introducing bioactive molecules and utilizing 3D bioprinting technology, researchers continue to optimize the properties of hydrogels to adapt to various wound conditions, which demonstrates great promise in the use of wound dressings. Taking the microenvironment of diabetic wounds into consideration, strategies for antibacterial, anti-inflammatory, immunomodulatory, antioxidant, and pro-angiogenic effects are integrated with multifunctional hydrogels. This paper systematically analyzes the existing challenges and explores the future research directions, and emphasizes the potential of multifunctional hydrogels in improving wound healing of diabetes and their clinical application prospects.Keywords: hydrogels, diabetic wound, multi-functional, wound dressing